2013
DOI: 10.1136/emermed-2013-202545
|View full text |Cite
|
Sign up to set email alerts
|

Frequent callers to and users of emergency medical systems: a systematic review

Abstract: It is unknown to what extent frequent callers impact upon EMS resources. Research should identify predictors and characteristics of frequent users of EMS, and a consistent definition of a frequent caller to or user of EMS would provide greater comparability. The lack of studies identified in this review suggests that further research is needed in order to inform policy and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 35 publications
2
73
0
5
Order By: Relevance
“…Although recent studies have investigated reasons behind frequent attendances at ED and why people in general call 999 on a single occasion, there exists little literature examining reasons behind frequent calls to ambulance services 8. One US study found frequent callers to an ambulance service to be characterised by male gender, black ethnicity, age over 35 years (particularly 45–54), behavioural health problems and chronic conditions including asthma and diabetes 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies have investigated reasons behind frequent attendances at ED and why people in general call 999 on a single occasion, there exists little literature examining reasons behind frequent calls to ambulance services 8. One US study found frequent callers to an ambulance service to be characterised by male gender, black ethnicity, age over 35 years (particularly 45–54), behavioural health problems and chronic conditions including asthma and diabetes 9.…”
Section: Introductionmentioning
confidence: 99%
“…Almost half of the repeat calls were related to patients aged 17–21 years, with repeat calls associated with a chief complaint of seizure, assault, suicide attempts, abdominal/chest pain, pregnancy and mental/behavioural problems. However, as noted by Scott et al ,8 the majority of the studies that have been conducted have focused on patients who were conveyed by ambulance, meaning that those who were not conveyed or who were not sent a response were excluded. Indeed, of three studies described above, only the first study9 included all frequent callers to the ambulance service, irrespective of whether they were conveyed.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing that the client values the relationship with his or her patients may help the social worker reflect to the provider the important pieces of their professional identity to frame therapeutic conversation. Further, if a client scores as a "thrill-seeker," the social worker may explore if the client is feeling fulfilled in their role, as an individual may enter the profession because of the excitement of saving lives and driving with lights and sirens, only to realize that dealing with the emergently ill or injured happens far less frequently than dealing with minor complaints, the elderly and chronically ill, and individuals that are abusing the system (Brokaw, Olson, Fullerton, Tandberg, & Sklar, 1998;Schaulis & Snoey, 2001;Scott, Strickland, Warner, & Dawson, 2013;Tangherlini, Pletcher, Covec, & Brown, 2010). Intuitively, EMS professionals experiencing stress who are also feeling unfulfilled in their occupation role are more likely to experience impaired work performance and/or leave the profession entirely, but that link should be the subject of future research.…”
Section: Implications For Practicementioning
confidence: 99%
“…Therefore, it is important to develop a more detailed knowledge about the psychiatric profile of patients attending the ED in order to tailor the care, both inside and outside the ED, according to the general or specific needs of people with mental health problems 19. The study of the characteristics of frequent users in ED could be useful for the planning of services4 and for a possible reduction in the number of visits 3. Whereas there are numerous studies of English-speaking countries, evidence for Europe is limited.…”
Section: Introductionmentioning
confidence: 99%